The night she went missing - Bird, Kristen (Mira, 2022)
"Emily, a popular but bookish prep school senior, goes missing after a night out with friends. She was last seen leaving a party with Alex, a football player with a dubious reputation. But no one is talking. Now three mothers, Catherine, Leslie, and Morgan, friends turned frenemies, have their lives turned upside down as they are forced to look to their own children--and each other's--for answers to questions they don't want to ask."--